2018
DOI: 10.1103/physrevlett.120.177801
|View full text |Cite
|
Sign up to set email alerts
|

Hard Competition: Stabilizing the Elusive Biaxial Nematic Phase in Suspensions of Colloidal Particles with Extreme Lengths

Abstract: We use computer simulations to study the existence and stability of a biaxial nematic N_{b} phase in systems of hard polyhedral cuboids, triangular prisms, and rhombic platelets, characterized by a long (L), medium (M), and short (S) particle axis. For all three shape families, we find stable N_{b} states provided the shape is not only close to the so-called dual shape with M=sqrt[LS] but also sufficiently anisotropic with L/S>9,11,14,23 for rhombi, (two types of) triangular prisms, and cuboids, respectively, … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

3
48
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 38 publications
(58 citation statements)
references
References 58 publications
(73 reference statements)
3
48
1
Order By: Relevance
“…It has been suggested that asymmetric placement of electric dipoles within the molecules might disrupt the tendency to smectic order and thus enhance the stability of N B (Querciagrossa, Berardi, and Zannoni 2018). The most recent simulations by Dijkstra's group(Dussi et al 2018) stress an important role of a strong shape asymmetry. The study focused on an entropy-driven colloidal suspension comprised of hard biaxial particles, characterized by a long ( L ), medium ( M ), and short ( S ) particle axes.…”
mentioning
confidence: 99%
“…It has been suggested that asymmetric placement of electric dipoles within the molecules might disrupt the tendency to smectic order and thus enhance the stability of N B (Querciagrossa, Berardi, and Zannoni 2018). The most recent simulations by Dijkstra's group(Dussi et al 2018) stress an important role of a strong shape asymmetry. The study focused on an entropy-driven colloidal suspension comprised of hard biaxial particles, characterized by a long ( L ), medium ( M ), and short ( S ) particle axes.…”
mentioning
confidence: 99%
“…One can distinguish between a (rodlike) prolate nematic phase (N þ ) when the longest particle axes are aligned along a common direction, and a (plateletlike) oblate nematic phase (N − ) when the shortest particle axes are aligned. Much work has since then been devoted to unveiling the rich variety of other nematic phases that can be stabilized by particles with different shapes and symmetries [16][17][18][19][20][21][22][23][24][25][26][27][28]. One of the first questions concerned the case of biaxial particles, for which the cylindrical symmetry is broken.…”
mentioning
confidence: 99%
“…In 1970 Freiser [16] showed by a generalized Maier-Saupe [29] theory that biaxial particles can exhibit a second-order phase transition from an isotropic to a biaxial nematic phase (N b ), in which both particle axes are aligned along two mutually orthogonal nematic directors. In the following years, the stability of the N b phase was theoretically predicted for hard biaxial particles of various shapes [27,[30][31][32].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Because our main interest is gaining an insight into the energetics associated to this process, the field strength is a simulation parameter that assumes values between * f ≡ f β = 0.1 and 3, with β the inverse temperature. At the same time, we propose an alternative route for the formation of the N B phase that does not necessarily imply extreme anisotropies [6] or particle size dispersities [8], nor the addition of depletants [10]. In the arXiv:1811.03677v1 [cond-mat.soft] 8 Nov 2018 following, we discuss the main aspects of the model and simulation methodology applied.…”
mentioning
confidence: 99%